Design of Mathematics Learning Strategies Pythagorean Theorem Material with Scientific Approach to Reduce Students' Misconceptions - IKBAL, IKBAL (EDUCTUM: Journal Research, 2022)
This study aims to find out mathematics learning with a scientific approach to student outcomes on pythagorean theorem material, and the subject of this study is students of class VIII-A at MTs Muhammadiyah Al-fatah Nangahale, school year 2020/2021. This research is a qualitative descriptive, research with data collection techniques using tests and questionnaires. The results of this study show that learning mathematics with scientific shortness can improve student outcomes, it can be seen from the percentage of pre-test results before using a scientific approach, namely students who understand as many concepts as possible 5 % and learners who don't understand as many concepts as 70 % and learners who experience as many misconceptions as possible 25 %. After using a scientific approach, the results of the percentage of students who understand the concept as much as 70 %, learners do not understand concepts as much as 15 % and learners who experience as many misconceptions as 15 %. So, the design of mathematics learning with a scientific approach, especially the material of the pythagorean theorem, can reduce the misconceptions of learners